2017
DOI: 10.1016/j.ultsonch.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of macauba and soybean oils as substrates for the enzymatic biodiesel production in ultrasound-assisted system

Abstract: The objective of this study is to evaluate the batch enzymatic production of biodiesel in solvent-free system under ultrasound using as substrates ethanol, soybean oil and macauba fruit oil. For this purpose, a Plackett & Burman experimental design was carried out for soybean oil while a 2 design was conducted for macauba oil in order to maximize the biodiesel conversion for each system. Good conversions to fatty acid ethyl esters (FAEE), 88% for soybean oil and 75.2% for macauba oil, was obtained thus demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…Biodiesel was produced in a solvent-free system under ultrasonication using ethanol, soybean oil or macauba fruit oil as a substrate, reaching a yield of 88% for soybean oil and 75.2% for macauba oil. 477 Biodiesel was produced in continuous mode using an ultrasound bath, com-paring N435 and Lipozyme TL-IM, and it was shown that Novozym-425 gave higher yields. 478 In another case, transesterification of Jatropha oil ( Jatropha curcas L.) with ethanol in a solvent-free system under microwave irradiation and comparing 7 lipases was reported.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“…Biodiesel was produced in a solvent-free system under ultrasonication using ethanol, soybean oil or macauba fruit oil as a substrate, reaching a yield of 88% for soybean oil and 75.2% for macauba oil. 477 Biodiesel was produced in continuous mode using an ultrasound bath, com-paring N435 and Lipozyme TL-IM, and it was shown that Novozym-425 gave higher yields. 478 In another case, transesterification of Jatropha oil ( Jatropha curcas L.) with ethanol in a solvent-free system under microwave irradiation and comparing 7 lipases was reported.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“…A similar study, on lipase catalyst and canola oil as raw material, was carried out by Bhangu et al concluding that ultrasound has reduced the reaction time from 22-24 hours to 1 hour [7]. Santin et al also confirms, in his studies, a 26% increase in yield when ultrasound is used to obtain biodiesel from soybean oil and macauba fruit oil with enzyme catalyst [8]. Sivaramakrishnan et al tested the effect of ultrasounds on three types of catalysts: acids, basics and enzymes in the production of biodiesel from microalgae.…”
mentioning
confidence: 58%
“…Our results show a similar behavior for the reactions with and without solvent under ultrasound application, suggesting that ultrasound itself was sufficient to improve the miscibility of the reaction mixture, favoring mass transfer between the substrate and the active site of the enzyme, turning irrelevant the use of the organic solvent (Trentin et al, 2015), and allowing the recovery of products without further complex purification processes (Dossat et al, 2002;Liu et al, 2008). The majority of reports in the literature in which the ultrasonic technology was employed in the enzymatic synthesis of biodiesel did not use solvents in the reactions, usually reporting excellent yields of conversion (Liu et al, 2008;Subhedar et al, 2015;Bhangu et al, 2017;Santin et al, 2017).…”
Section: Effect Of Solvent Tert-butanolmentioning
confidence: 99%
“…Evaluating the kinetics of the ultrasound assisted transesterification reaction catalyzed by combi-lipase, yields of conversion of ethyl esters of about 75 % in 5 h reaction were observed in the present work. Santin et al (2017) and Gharat and Rathod (2013) analyzed the ultrasound transesterification reaction catalyzed by the enzyme CALB, obtaining conversions of about 88 % for soybean oil and 87 % for waste cooking oil in 4 h of reaction, respectively (Gharat and Rathod, 2013;Santin et al, 2017). However, one of the advantages of using the combi-lipase compared with CALB used individually is the reduction of the process cost, since this enzyme has a very high commercial price when compared to the others, costing 16 times more than TLL, as an example (Li et al, 2010).…”
Section: Comparisons Of Combi-lipase and Individually Lipasesmentioning
confidence: 99%
See 1 more Smart Citation